Strawberry Generation: The role of parental attachment, friendship quality, and mental health self-efficacy on adolescent self-resilience - Pramudita, Aisyah; Latifah, Melly; Riany, Yulina Eva (Faculty of Psychology, Universitas Diponegoro, 2025)
Background: Strawberry generation is one of the phenomena that exists in adolescents today. The term ‘strawberry generation’ refers to adolescents who are creative but fragile and easily overwhelmed. This condition is supported by found which 1:7 adolescent aged 10-19 years experience mental disorders. The mental health influenced by resilience. Adolescents with low self-resilience show an increased risk of anxiety and depression symptoms in young adulthood.Purpose: This study aims to reveal how parental attachment, friendship quality, and mental health self-efficacy affect adolescent’s resilience. Mental health self-efficacy has limited research in Indonesia, this variable became novelty of this study.Method: This study used a quantitative approach with an explanatory method, the research sample was 398 high school students in Bogor City with random sampling on school determination, the data obtained then went through statistical tests with SPSS to get correlation and multiple linear regression result.Findings: parental attachment, friendship quality, and mental health self efficacy simultaneously affect adolescent self-resilience by 28. 7 percent. Factor that significantly affect adolescent self-resilience are adolescent gender, friendship quality, and mental health self-efficacy.Implication: This research can serve as a base for the development of resilience improvement programs in the community (family, school and government).